The alloys of iron and tungsten - Gregg, J. L. (Alloys of iron research. Monograph series, 1934)
Introduction - Constitution of iron-tungsten alloys - Preparation and properties of iron-tungsten alloys - Iron-carbon and tungsten-carbon alloys - Constitution of iron-tungsten-carbon alloys - Manufacture of tungsten steels - Characteristics of tungsten steels - Mechanical properties of tungsten steels - Tungsten magnet steels - Tungsten in cast iron and steel - Tungsten in tool and die steels - Development of high-speed steels - The nature of high-speed steels - Cutting properties of high-speed steels - Other properties of high-speed steels - Miscellaneous alloys containing tungsten.